Estimation of Chromatographic Columns Performances using Computer Tomography and CFD Simulations - Schmidt, Irma; Lottes, Florian; Minceva, Mirjana; Arlt, Wolfgang; Stenby, Erling H. (Chemie Ingenieur Technik, 2011)
The flow inside a chromatographic column depends decisively on the packed bed inside. Non-destructive X-ray computed tomography (CT) was applied as a novel measurement technique to visualize the distribution of velocity and axial dispersion coefficients in preparative scale columns. The results show, that spherical particles seem to be more efficient than irregular ones in terms of HETP, which has to be partly a result of the more homogeneous flow profile they induce. The prediction of column performance in dependence of the structure of the packed bed was simulated by CFD (Computational Fluid Dynamics), using a model which besides the hydrodynamics parameters attained by CT also includes adsorption isotherms and mass transfer parameters. The results of the CFD simulation shall help to establish rules for selecting the right adsorption material for a given separation task in advance.
Keywords: CFD; Chromatography; Column; Computer tomography

Evaluation of Formic-Acid-Based Hydrogen Storage Technologies - Schmidt, Irma; Müller, Karsten; Arlt, Wolfgang (Energy & Fuels, 2014)
To make hydrogen a feasible energy carrier, its transformation into another chemical is advisible. Formic acid may constitute an attractive option to store hydrogen in a dense and safe form. The efficiency of formic-acid-based process chains for the storage of hydrogen energy has been evaluated. The efficiency is highly dependent upon the way formic acid is produced. Options based on reactions of hydrogen with carbon dioxide show a rather poor energetic performance, while routes using renewable production of intermediate carbon monoxide can reach competitive efficiencies. For the storage of electrical energy, an overall efficiency of about 12% is possible using the current state of the art technology, but alternative processes show potential for higher efficiencies.

Selection of stationary phase particle geometry using X-ray computed tomography and computational fluid dynamics simulations - Schmidt, Irma; Minceva, Mirjana; Arlt, Wolfgang (Journal of Chromatography A, 2012)
The X-ray computed tomography (CV) is used to determine local parameters related to the column packing homogeneity and hydrodynamics in columns packed with spherically and irregularly shaped particles of same size. The results showed that the variation of porosity and axial dispersion coefficient along the column axis is insignificant, compared to their radial distribution. The methodology of using the data attained by CT measurements to perform a CFD simulation of a batch separation of model binary mixtures, with different concentration and separation factors is demonstrated. The results of the CFD simulation study show that columns packed with spherically shaped particles provide higher yield in comparison to columns packed with irregularly shaped particles only below a certain value of the separation factor. The presented methodology can be used for selecting a suited packing material for a particular separation task. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Chromatography; Stationary phase; Particle geometry; X-ray computed tomography; CFD simulation